Journalism in Crisis? - Russial, John; Laufer, Peter; Wasko, Janet (Javnost-The Public, 2015)
This article considers several questions pertaining to the current state of journalism. The discussion explores the meaning of journalism and journalists, as well as considering the role of journalists in an increasingly digital environment. The article concludes by exploring journalism in the future and why this all matters. A major theme of this discussion (and the articles in this special issue) is whether journalism is currently in crisis. Finally, an example is offered exemplifying the complexity of issues that surround journalism today.